Pengaruh Upah Minimum Provinsi dan Tingkat Pengangguran terhadap Penyerapan Tenaga Kerja di Provinsi Aceh - Cut Hasranda; Isthafan Najmi; Yuliana Yuliana; Edwar M.Nur; Cut Megawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
: This research is partially and simultaneously to determine the effect of the provincial minimum wage and unemployment rate simultaneously on the absorption of labor in Aceh Province. The research location is in Aceh Province, while the research object is the provincial minimum wage and unemployment rate on the absorption of labor in Aceh Province. The sampling technique method used the census method. The data analysis method used in this research is multiple linear regression. The number of years in this study was 6 years with a census sampling technique. The results of the study prove that simultaneously shows that the provincial minimum wage and the unemployment rate have an effect on increasing employment in Aceh Province with an Fcount of 32.767, while Ftable at a significance level of = 5% is 3.186., then the results of the study show that partially The provincial minimum wage variable with a regression coefficient of 0.216 has an effect on employment in Aceh Province and the results show that partially the unemployment rate variable with a regression coefficient of 0.116 also affects employment in Aceh Province